Covid-19 dan Perpustakaan: Sebuah Literature Review - Rochani Nani Rahayu (Media Pustakawan, 2021)
The covid-19 outbreak in the world and in Indonesia since last March 2020, has caused the activities of most people to be carried out from home. The library is an institution that is obliged to carry out work from home. Therefore, a study was conducted to determine the activities carried out during the covid-19 pandemic. This research uses the literature review method. The data source used was EBSCOhost which was accessed fro the E-Resources of the National Library of Indonesia on May 6, 2020. The search used the keyword covid-19 and objectives. The data obtained from the search results are then analyzed against each article with the aim of solving and identifying important information contained therein. Furthermore, the synthesis of all the articles obtained is carried out, namely integrating and identifying conclusions that can be drawn from all articles. Based on the results obtained, it can be concluded that abroad, during the covid-19 pandemic, both public libraries, college libraries, although there are some closed, there are those who postpone activities, but they still provide services to users by utilizing various information technology platforms and social media. In addition to providing information services to users, libraries even provide infrastructure to be used as a place to distribute aid resources to communities affected by covid-19. The experiences of several librarians who are involved in the response to covid-19, such as the participation of a librarian in providing face shield can provide information to the public that librarians are also contributing to the prevention of the covid-19 outbreak.